Ceremonia de Profesor Honorario de la PUCP del Dr. César Camacho Manco - Carranza Saravia, César Augusto (1997)
De izquierda a derecha: 1° César Carranza, 2° Jean-Christophe Yoccoz, 3° Uldarico Malaspina, 4° César Camacho Manco, 5° José Luis Aroca